2022
DOI: 10.1097/ccm.0000000000005558
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Implementing Targeted SEDation in Mechanically Ventilated Emergency Department Patients: The ED-SED Pilot Trial

Abstract: Deep sedation in the emergency department (ED) is common, increases deep sedation in the ICU, and is negatively associated with outcome. Limiting ED deep sedation may, therefore, be a high-yield intervention to improve outcome. However, the feasibility of conducting an adequately powered ED-based clinical sedation trial is unknown. Our objectives were to assess trial feasibility in terms of: 1) recruitment, 2) protocol implementation and practice change, and 3) safety. Patient-centered clinical outcomes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The study included patients who received an NMBA for endotracheal intubation or postintubation care. The investigation was a secondary analysis of a larger, multicentre, prospective trial 4. The primary outcome, AWP, was assessed using a modified Brice Questionnaire that was administered during the hospital stay or through a phone call after discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The study included patients who received an NMBA for endotracheal intubation or postintubation care. The investigation was a secondary analysis of a larger, multicentre, prospective trial 4. The primary outcome, AWP, was assessed using a modified Brice Questionnaire that was administered during the hospital stay or through a phone call after discharge.…”
Section: Methodsmentioning
confidence: 99%
“…This was a single-center, secondary cohort analysis of individual patient-level data from prior clinical trials and cohort studies, each of which has been previously published (10,11,(14)(15)(16)(17)(18)(19)(20)(21), and conducted at a tertiary, academic medical center. The preintervention group was composed of patients managed before ED-based lung-protective ventilation was instituted (10,11,(14)(15)(16).…”
Section: Study Setting and Designmentioning
confidence: 99%
“…In 2012, Shehabi et al (8) demonstrated that early deep sedation was an independent risk factor for delayed extubation, hospital death, and 180-day mortality and the authors’ previous work identifies ED sedation as an important factor in ICU clinical outcomes (9). The study by Fuller et al (7) serves as a natural next step in questioning whether ICU outcomes in patients with respiratory failure can potentially be impacted by care that is delivered before arrival to the ICU. In this issue by Critical Care Medicine , the study by Fuller et al (7) confirm that there is wide variability in ED sedation depth documentation and supports the notion care provided in the ED impacts the arc of care for the critically ill.…”
mentioning
confidence: 99%
“…The study by Fuller et al (7) serves as a natural next step in questioning whether ICU outcomes in patients with respiratory failure can potentially be impacted by care that is delivered before arrival to the ICU. In this issue by Critical Care Medicine , the study by Fuller et al (7) confirm that there is wide variability in ED sedation depth documentation and supports the notion care provided in the ED impacts the arc of care for the critically ill.…”
mentioning
confidence: 99%
See 1 more Smart Citation